COVID-19 Pandemic and Resilience of the Transnational Home-Based Elder Care System between Poland and Germany. Issue 4 (3rd September 2021) - Nowicka, Magdalena; Bartig, Susanne; Schwass, Theresa; Matuszczyk, Kamil
ABSTRACT: As COVID-19 puts older people in long-term institutional care at the highest risk of infection and death, the need for home-based care has increased. Germany relies largely on migrant caregivers from Poland. Yet the pandemic-related mobility restrictions reveal the deficiencies of this transnational elder care system. This article asks if this system is resilient. In order to answer this question, the research team conducted interviews with 10 experts and randomly selected representatives of brokering and sending agencies in Germany and Poland. We interviewed 13 agencies in Germany and 15 in Poland on the agencies' characteristics, recruitment strategies, challenges of the pandemic, and impact of legal regulations in the sector. The analysis shows that the system could mobilize adaptive capacities and continue to deliver services, but its absorptive capacity is limited. To enhance resilience, policies working toward formalization and legalization of care services across national borders are required.